(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Brakes squeal has remained to be one of the major NVH challenges in brake system design and development. It has been a concern for automotive industry for decade. Brake researchers have proposed many brake squeal reduction and prevention methods in order to overcome and reduce the squeal that emanates from the brake disc systems. In this paper, the effectiveness of constrained layer dampers (CLD) in reducing disc brake squeal noise was investigated. CLD isolates the brake squeal noise through shear deformations of the viscoelastic materials. Two sets of brake tests were conducted using the brake test dynamometer with the application of CLD. Two different types of CLD were used which are three-layer constrained layer damper and four-layer constrained layer damper. Squeal tests were carried out using brake noise test rig based on the global standard procedure SAE J2521. From the test, four-layer CLD configuration works more efficient than three-layer CLD configuration. CLD made up of nitrile butadiene rubber, silicone rubber and mild steel proved to be the most effective noise insulator at hydraulic pressure range of 5 bar to 30 bar and temperature range of 50oC to 200oC with a maximum noise reduction of 11.3 dBA. Thus, CLD technique was proven to be an effective method in reducing brake squeal noise.